The quality of accounting earnings and change in political power map: evidence from Indonesia - Harymawan, Iman; Agustia, Dian; Prasetyo, Khusnul (2017)
This study investigates the earnings quality of politically connected firms listed in Indonesian Stock Exchange during 2006-2010. This study compare two definition (Soeharto Dependency Index (SDI) and Politically Exposed Person (PEP)) of political connections to capture the effect of the changes of political power map on the earnings quality of politically connected firms in Indonesia.The finding shows that the quality of accounting earnings of politically connected firms which were formerly closely related to President Soeharto in 1998 are not significantly different to other firms.Furthermore, when this study employ politically exposed person as a proxy of political connections, the findings shows that connected firms have significantly lower quality accounting earnings.Consistent with prior findings, this study shows that change in political power map in Indonesia affect the level of earnings quality of politically connected firms.